The External Wealth of Nations Mark II : Revised and Extended Estimates of Foreign Assets and Liabilities, 1970-2004 - Lane, Philip (IMF Working Papers; Working Paper ;, 2006)
We construct estimates of external assets and liabilities for 145 countries for the period 1970-2004. We describe our estimation methods and present key features of the data at the country and the global level. We focus on trends in net and gross external positions, and the composition of international portfolios, distinguishing between foreign direct investment, portfolio equity investment, official reserves, and external debt. We document the increasing importance of equity financing and the improvement in the external position for emerging markets, and the differing pace of financial integration between advanced and developing economies. We also show the existence of a global discrepancy between estimated foreign assets and liabilities, and identify the asset categories that account for this discrepancy.